The Incorporation of Higher Order Thinking Skills in Ruangguru Application for Senior High School Tenth Graders - Fulky Aulia; Sudarya Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
This study is a content analysis that attempts to analyze the incorporation of higher-order thinking skills based on Bloom’s revised taxonomy in English multiple-choice questions for tenth graders at Ruangguru application. Ten chapters of English subject for tenth graders including 120 randomly selected questions in the English exercises at the application were chosen as data source of this study. The findings show that the questions incorporate the order thinking skills with a percentage of 50,8% of lower-order thinking skills (LOTS) and 49,2% of higher-order thinking skills (HOTS), which means that both are not evenly distributed in every chapter. The most dominant level found in this study is evaluation, which includes checking and critiquing, with a percentage of 25,8%. The incorporation of HOTS in Ruangguru application has been proven, but the result cannot be generalized since not all students in Indonesia use the application. Thus, HOTS analysis to other learning applications, other grades, and/or other subjects are encouraged to be conducted to picture out the incorporation of HOTS in greater coverage.